Corionicidade e complicações perinatais. - Isabel Ferreira; Carla Laureano; Miguel Branco; Ana Nordeste; Margarida Fonseca; Adelaide Pinheiro; Maria Isabel Silva; Maria Céu Almeida (Acta Médica Portuguesa, 2005)
Considering the highest rate of morbidity and mortality in diamniotic monochorionic twins, the authors evaluated and compared the adverse obstetric and perinatal outcome in twin pregnancies according to chorionicity.A retrospective study was conducted in all twin deliveries that occurred in the Obstetric Unit of Maternidade Bissaya-Barreto, for a period of tree years (from the 1st of January 1999 until the 31st of December 2001). From de 140 diamniotic twin pregnancies studied, we considered two groups according to the chorionicity: monochorionic and dichorionic. We compared multiple parameters as, epidemiologic data, adverse obstetric outcome, gestacional delivery age, type of delivery and the morbidity, the mortality and the follow-up of the newborn. The statistic tests used were the X2 and the t student.From the 140 twin pregnancies included in the study, 66% (92 cases) presented dichorionic placentation and 34% (48 cases) were monochorionic. In the group of monochorionic pregnancies, we observed highly difference related to pathology of amniotic fluid (14.5% vs 2.2%), discordant fetal growth (41.6% vs 22.8%) and rate of preterm delivery (66.6% vs 32.6%). Related to the newborn we verified that they had a lower average birth weight (1988g vs 2295g), a highly rate of weight discordancy (23% vs 15.3%), intraventricular haemorrhage (2.2% vs 0%) and IUGR (6.6% vs 1.6%), statistically significant in the monochorionic group. Also the perinatal mortality rate was significantly higher in the monochorionic pregnancies (93.7 per thousand vs 21.7 per thousand).The high rate of morbidity and mortality related to the monochorionic twin pregnancies, implies the need of a correct identification of the type of chorionicity and also a high standard of prenatal surveillance in prenatal specialised health centers.